The Judicial Reasoning Behind Decision No. 262/Pid.B/2018/Pn.Skt on a Case of Mass Violence: The Perspective of Human Aggressiveness and the Ashobiyah Terminology - Purwadi Wahyu Anggoro; Khudzaifah Dimyati; Absori; Kelik Wardiono; Waljinah, Sri (Universitas Muhammadiyah Surakarta, 2023)
ABSTRACT Purpose of the study: This research aimed to analyze the judicial rationing behind Decision No. 262/Pid.B/2018/Pn.Skt. According to Article 170 of the Indonesian Criminal Code in the legal event of a mass violence crime that occurred in Surakarta City. Methodology: This was normative legal research that used the case approach. It emphasized the legal consideration of judges in deciding and giving a verdict upon a case. Results: This research analyzed Decision No. 262/Pid.B/2018/Pn.Skt. Judges considered that the actions committed by the group of perpetrators originated from the aggressive nature of humans due to their animal power that can cause law-violating actions. This aggressive human nature in a group caused a sense of affection and bond creates similarities in desires, goals, and ideas. It resulted in a sense of solidarity in the group according to the ashobiyah terminology. Applications of this study: to provide knowledge on: (1) the judicial analysis based on the factors that influence the occurrence of mass violence; and (2) the judicial consideration in deciding upon a case of mass violence in Surakarta City based on the judicial rationing in Decision No. 262/Pid.B/2018/PN.Skt. Novelty/Originality of this study: This paper provided new information on the action of mass violence on Decision No. 262/Pid.B/2018/PN.Skt correlated with Ibnu Khaldun’s ashobiyah terminology. Keywords: judicial reasoning, mass violence, aggressivity, ashobiyah